Regulation of Cell Component Production by Growth Rate in the Group B Streptococcus - Ross, Robin A. (American Society for Microbiology, 1999)
Group B Streptococcus (GBS) is the leading cause of bacterial sepsis and meningitis among neonates. While the capsular polysaccharide (CPS) is an important virulence factor of GBS, other cell surface components, such as C proteins, may also play a role in GBS disease. CPS production by GBS type III strain M781 was greater when cells were held at a fast (1.4-h mass-doubling time [t(d)]) than at a slow (11-h t(d)) rate of growth. To further investigate growth rate regulation of CPS production and to investigate production of other cell components, different serotypes and strains of GBS were grown in continuous culture in a semidefined and a complex medium. Samples were obtained after at least five generations at the selected growth rate. Cells and cell-free supernatants were processed immediately, and results from all assays were normalized for cell dry weight. All serotypes (Ia, Ib, and III) and strains (one or two strains per serotype) tested produced at least 3.6-fold more CPS at a t(d) of 1.4 h than at a t(d) of 11 h. Production of beta C protein by GBS type Ia strain A909 and type Ib strain H36B was also shown to increase at least 5.5-fold with increased growth rate (production at a t(d) of 1.4 h versus 11 h). The production of alpha C protein by the same strains did not significantly change with increased growth rate. The effect of growth rate on other cell components was also investigated. Production of group B antigen did not change with growth rate, while alkaline phosphatase decreased with increased growth rate. Both CAMP factor and beta-hemolysin production increased fourfold with increased growth rate. Growth rate regulation is specific for select cell components in GBS, including beta C protein, alkaline phosphatase, beta-hemolysin, and CPS production.